2015
DOI: 10.1016/j.jip.2015.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial diseases in marine bivalves

Abstract: Bivalve aquaculture is seriously affected by many bacterial pathogens that cause high losses in hatcheries as well as in natural beds. A number of Vibrio species, but also members of the genera Nocardia and Roseovarius, are considered important pathogens in aquaculture. The present work provides an updated overview of main diseases and implicated bacterial species affecting bivalves. This review focuses on aetiological agents, their diversity and virulence factors, the diagnostic methods available as well as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
130
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(131 citation statements)
references
References 233 publications
(337 reference statements)
1
130
0
Order By: Relevance
“…Parasites and pathogens have induced the collapse of numerous populations of exploited bivalves [50; 51]). A population of parasites can grow from several individuals to thousands of individuals within several months in an aquaculture setting, where predators are absent [52].…”
Section: Discussionmentioning
confidence: 99%
“…Parasites and pathogens have induced the collapse of numerous populations of exploited bivalves [50; 51]). A population of parasites can grow from several individuals to thousands of individuals within several months in an aquaculture setting, where predators are absent [52].…”
Section: Discussionmentioning
confidence: 99%
“…Third, since 2012, the number of reported cases of adult mortalities associated with the presence of V. aestuarianus has increased considerably [79]. Interestingly, during the 2008-2012 period, this bacterial species had been rarely isolated from moribund oysters, suggesting the possible (re)emergence of V. aestuarianus as an oyster pathogen.…”
Section: Box 1 Mortality Outbreaks In Crassostrea Gigasmentioning
confidence: 99%
“…It has also been demonstrated that the virus is neither essential nor sufficient to cause juvenile deaths, whereas bacteria are necessary for the disease process [7]. This emphasizes the need to investigate the role of bacteria, particularly vibrios, in this disease.Third, since 2012, the number of reported cases of adult mortalities associated with the presence of V. aestuarianus has increased considerably [79]. Interestingly, during the 2008-2012 period, this bacterial species had been rarely isolated from moribund oysters, suggesting the possible (re)emergence of V. aestuarianus as an oyster pathogen.…”
mentioning
confidence: 99%
“…RLOs were first detected in marine bivalves in the 1970s (Harshbarger, Chang, & Otto, ). They are typically transmitted directly between hosts via water‐borne transmission and may be found free within host cell cytoplasm or within intercytoplasmic vacuoles (Friedman & Crosson, ; Travers Boettcher Miller, Roque, & Friedman, ). Although RLO infections in teleost fish have been extensively studied (Rozas & Enríquez, ; Stride, Polkinghorne, & Nowak, ), those affecting molluscs, other than the RLO causing withering syndrome in abalone, have not (Tavers et al., ).…”
mentioning
confidence: 99%